The Clustering of Financial Services in London - Gary A. S. Cook; Naresh R. Pandit; Jonathan V. Beaverstock; Peter J. Taylor; Kathy Pain (European Regional Science Association (ERSA), 2004)
This paper reports a one-year study which investigated the clustering of financial services activity in London. A questionnaire asking about the advantages and disadvantages of a London location was sent to a stratified sample of 1,500 firms and institutions. In addition, thirty-nine on-site interviews with firms, professional institutions, government bodies and other related agencies were conducted. The study finds that banking, including investment banking, forms the cluster's hub with most other companies depending on relationships with this sub-sector. Generally, the cluster confers many advantages to its incumbents including enhanced reputation, the ability to tap into large, specialized labor pool and customer proximity. The localized nature of relationships between skilled labor, customers and suppliers is a critical factor which helps firms achieve innovative solutions, develop new markets and attain more efficient ways to deliver services and products. Particularly important are the personal relationships which are enhanced by the on-going face-to-face contact that is possible in a compact geographical space. Many of the cluster's advantages are dynamic in that they become stronger as agglomeration increases. The study also finds important disadvantages in the cluster which threaten its future growth and prosperity. These include the poor quality and reliability of transport, particularly the state of the London Underground and links to airports, increasing levels of regulation and government policy that is not co-ordinated with the whole of the cluster in mind. Key words: Industrial clustering, agglomeration, financial services.
Keywords: 330; Industrial clustering; agglomeration; financial services